Evaluating the role of dental education in shaping aesthetic preferences and clinical choices in Cambodia - Pisethsathya, Chhean; Chamroeun, Chhim; Samnang, Phav; Marya, Anand; Tabnjh, Abedelmalek Kalefh; Selvaraj, Siddharthan (Frontiers in Oral Health, 2025)
AimThe aim of this study is to evaluate and compare the factors influencing perceived dental appearance among dental and non-dental university students.MethodsA questionnaire was provided to all the consenting participants in the study. The survey was validated with a pilot study and the results of the pilot study were not included in the final results. A total of 420 participants were recruited for the study, of which 210 were dental students and 210 were non-dental students. The recruited participants answered questions regarding smile and esthetics perceptions using a validated questionnaire.ResultsSignificant differences were observed between groups in perceptions of facial and dental aesthetics, with non-dental students placing more importance on features like nose shape (P = 0.038) and white or specific tooth shapes (P < 0.05). Dental students showed greater awareness of dental alignment but reported lower overall satisfaction. Non-dental students had higher aesthetic treatment experience and intentions (P < 0.05), brushed more frequently, but flossed and visited the dentist less often. Overall, non-dental students had significantly higher satisfaction scores than dental students (P < 0.001).ConclusionIt was observed that both dental and non-dental students had a good awareness on esthetics; however, dental students showed greater sensitivity towards aesthetics due to their deeper knowledge and educational background. On the other hand, non-dental students due to their superficial knowledge regarding dentistry had higher expectations from dental treatment and expressed unrealistic esthetic demands.